REVIEW ON THE ROLE OF NANOPARTICLES IN OVERCOMING DRUG RESISTANCE IN CANCER: MECHANISTIC AND THERAPEUTIC PERSPECTIVES (Journal of Medical & Health Sciences Review, 2025)
Nanoparticles have emerged as a transformative platform in cancer therapeutics due to their unique physicochemical properties and ability to overcome the limitations of conventional chemotherapy. This review offers a thorough explanation of nanoparticles, their categorization, and their molecular functions in the fight against cancer treatment resistance. Metal-based, ceramic, and carbon-based nanostructures are examples of the organic and inorganic forms of nanoparticles, each of which offers unique physicochemical properties for targeted drug delivery. While inorganic and metallic nanoparticles offer better stability, controlled release, and imaging potential, organic nanoparticles like liposomes and polymeric carriers improve biocompatibility and drug solubility. Targeted drug delivery, improved permeability and retention effects, and regulated intracellular release that reduces systemic toxicity are the processes of nanoparticle-mediated cancer therapy. Both intrinsic and extrinsic mechanisms, such as altered drug efflux, apoptotic inhibition, tumor hypoxia, and enzymatic degradation of anticancer medicines, can lead to drug resistance in cancer. Collectively, this review highlights the pivotal role of nanotechnology in redefining strategies to overcome cancer drug resistance and enhance treatment outcomes.